Self Management of Chronic Disease Alzheimer's Disease - Bährer-Kohler, Sabine (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Alzheimer's Disease (AD) is a disease which is increasing worldwide. Treatment can modify its course but cannot cure it yet. AD is an enormous challenge not only for the afflicted person. This book contains articles by internationally recognized authors from different professional backgrounds coming from European, Asian and African countries as well as from Switzerland. The book begins with basic information about chronic disease, self-management, aging and dementia. Further chapters deal with care and self-management, including end-of-life aspects. The authors focus on training programs used around the world in general, and focus in particular on self management programs for persons suffering from AD and their caregivers. The book addresses the applicability and economic consequences of these programs. It might be helpful if an issue as important as self-management of chronic diseases, especially AD, were to find its way into the daily life of patients and their caregivers as well as into treatment worldwide.